Induced gamma oscillations index individual differences in speech sound perception and production. (December 2018) - Ou, Jinghua; Law, Sam-Po
Abstract: Auditory neuroscience has provided strong evidence that neural oscillations synchronize to the rhythm of speech stimuli, and oscillations at different frequencies have been linked to processing of different language structures. The present study aims to examine how these ubiquitous neurophysiological attributes may inform us about the brain processes that underpin individual differences in speech perception and production, which in turn elucidate the specific functions of neural oscillations in the domain of speech processing. To this end, we recorded electrophysiological responses to a lexical tone contrast in a passive auditory oddball paradigm from two groups of healthy tone-language speakers who were equal in perceptual discriminability but differed in response latency and production distinctiveness of the tone contrast. Time-frequency analysis was applied to the EEG data, and decomposed into theta (4–7 Hz), beta (12–30 Hz), and gamma (30–50 Hz) frequency bands. Results show that listeners with longer discrimination RT and less distinctive production showed significantly higher induced (non-phase-locked) gamma during tone processing. Moreover, among speakers with less distinctive production, individual differences in induced gamma were significantly correlated with discrimination latency and production distinction. Based on the present findings, we propose that differences in gamma oscillations reflect differential sensory/perceptual computations during acoustic encoding, impacting the quality of perceptual representations, which further mediates individual differences in speech perception and production. Highlights: Subtle individual differences in speech processing can be revealed by induced EEG. Induced gamma reflects differences in sensory computation during acoustic encoding. Induced gamma correlates with response times in a speech discrimination task. Induced gamma correlates with acoustic distinctions in speech production. Induced gamma mediates between perception and production performance.